2014
DOI: 10.1007/s10464-014-9668-9
|View full text |Cite
|
Sign up to set email alerts
|

Low Prospects and High Risk: Structural Determinants of Health Associated with Sexual Risk Among Young African American Women Residing in Resource‐Poor Communities in the South

Abstract: African American women at increased risk of HIV/sexually transmitted infection (STI) may engage in risky sex as a coping mechanism for depressed economic conditions. This study examines the association between high-risk sexual behavior and structural determinants of sexual health among a sample of young African American women. 237 young African American women (16-19 years old) from economically disadvantaged neighborhoods in North Carolina were enrolled into a randomized trial testing the efficacy of an adapte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
45
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 46 publications
3
45
0
Order By: Relevance
“…These findings are consistent with previous research indicating associations between African American/Black race [3–5] and unstable housing [19,24,25] and STIs. It is also well documented that unstable housing is consequence of low socioeconomic status, which is associated with increased sexual risk and STIs.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…These findings are consistent with previous research indicating associations between African American/Black race [3–5] and unstable housing [19,24,25] and STIs. It is also well documented that unstable housing is consequence of low socioeconomic status, which is associated with increased sexual risk and STIs.…”
Section: Discussionsupporting
confidence: 93%
“…However, increasingly, researchers have called for broader perspectives to account for social determinants and environmental influences on STI risk and acquisition [22,23]. As such, a growing body of research has examined social, environmental, and other contextual factors associated with STI-related risk among AYAs, including influences related to housing instability or homelessness [19,24,25], unemployment [26], and exposure to community violence [27]. Yet, there is still limited research focused specifically on social-environmental contextual influences related the acquisition of STIs among AYAs [13,26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Population-based studies in diverse regions have shown that food insecurity is associated with inconsistent condom use [1015], sexual exchange [10], multiple sexual partnerships [13,14,16], a lack of control in sexual relationships [10], sexual relations with older or gang-affiliated partners [16], sexual violence [17], symptoms consistent with sexually transmitted infections [12,15] and substance use before sex [16]. Some of these links were demonstrated in resource-rich settings [11,13,16].…”
Section: Introductionmentioning
confidence: 99%
“…Some of these links were demonstrated in resource-rich settings [11,13,16]. In San Francisco, food insecurity was longitudinally associated with unprotected sexual activity and having multiple sexual partners among 154 homeless and marginally housed PLHIV [13].…”
Section: Introductionmentioning
confidence: 99%